Following Germany's Lead : Using International Monetary Linkages to Identify the Effect of Monetary Policy on the Economy - Julian di Giovanni; Justin McCrary; Till von Wachter (Institute for the Study of Labor (IZA), 2005)
Forward-looking behavior on the part of the monetary authority leads least squares estimates to understate the true growth consequences of monetary policy interventions. We present instrumental variables estimates of the impact of interest rates on real output growth for several European countries, using German interest rates as the instrument. We compare this identification strategy to the vector autoregression approach, and give an interpretation of our estimates that is appropriate in a dynamic context. Moreover, we show that the difference between least squares and instrumental variables estimates provides bounds for the degree of endogeneity in monetary policy. The results confirm a considerable downward bias of estimates that do not account for potential forward-looking monetary policy decisions. The bias is higher for countries whose monetary policy was more independent of Germany.
Keywords: J60; E52; 330; monetary policy; forward looking bias; instrumental variables; Geldpolitik; Zinspolitik; Deutsch; Konjunkturzusammenhang; Erwartungstheorie; Schätzung; EU-Staaten; Deutschland